(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Duplex stainless steels have approximately equal amount of ferrite and austenite, due to an accurate control of chemical composition and thermo-mechanical treatment. This phase balance allows the best combination of mechanical and corrosion resistance properties. Alloy 2205 DSS exhibits an excellent combination of both strength and corrosion resistance, the approximate 50/50 ferrite-austenite structure provides excellent chloride pitting and stress corrosion cracking resistance but lack wear resistance. Nitrogen Plasma techniques perform an unrivaled way to improve the surface characteristic of materials used in medical and biology application. This technique is very important used in many industries to change the surface characteristics of the material used in medical applications at different parameter with different parameters at vacuum chamber of air (2mbar), 680 volt and 30 mA .Use different time for plasma nitriding (5, 15 and 25) hrs on the chemical structure of 2205 DSS alloy and the form of phases was investigated using OM, FESEM with EDS, XRD, and antibacterial test, tafel potential polarization and cyclic polarization for biomedical application. The results indicate the formation of layers and phases S, Fe3N, and Fe2-3N were formed on the alloy’s surface, which would improve mechanical properties and corrosion resistance in Ringer solution at 37 ◦C.